Measurement of talar morphology in northeast Chinese population based on three-dimensional computed tomography. Issue 37 (September 2019) - Han, Qing; Liu, Yang; Chang, Fei; Chen, Bingpeng; Zhong, Lei; Wang, Jincheng
Abstract : Abstract: Morphological data of talus are important for the design of talar prostheses. The talar morphology of Chinese population has been rarely reported. This study adopted a three-dimensional (3D) measurement approach to provide accurate data for the anatomical morphology of talus in Northeast Chinese population and compared it with that of foreigners. One hundred forty-six healthy subjects form Northeast China underwent computed tomography (CT) arthrography. 3D digital talar model was reconstructed and thirteen morphological parameters were measured through Mimics and Magics software. Length and breadth indexes of total talus, trochlea, medial and lateral malleolus articular surface were mainly selected. Statistical analysis was conducted by independent-samples and paired-samples t test through SPSS software. All the indexes were normally distributed. No significant difference between left and right talus was identified in either males or females ( P > .05). Most of the indexes showed significant sexual differences except the radian of lateral malleolus articular surface and the posterior breadth of trochlea ( P < .05). The talar anatomy of Chinese subjects is different from the published data in other populations. The promising approach adopted in this study addresses some inconvenience with previous conventional methods on cadaver specimens. The geometric parameters of talus in Chinese population differ from those in other populations. The talar measurements and morphology analysis in this study suggest that population characteristics should be taken into account. This study will provide references for the design of talar prostheses in Chinese population.